2018
DOI: 10.1177/1045389x18799493
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a large-scale magnetorheological elastomer–based vibration isolator for highway bridges

Abstract: This study presents an experimental investigation on the magnetorheological effect of a new magnetorheological elastomer–based adaptive bridge isolation bearing system. Two identical magnetorheological elastomer–based adaptive bridge bearings (isolators) were designed and fabricated. Electromagnets were incorporated to create a closed-loop magnetic path in the magnetorheological elastomer layers. A double-lap shear and compression test setup was utilized to characterize the mechanical properties of the system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Therefore, the block-up behavior can be avoided by properly controlling the pressure difference (or the fielddependent actuating force) through the servo valve system. It is remarked here that recently, a new kind of high-loaded mount using MR elastomer was introduced in Yarra et al (2018). The mount based on the MR elastomer does not require any fluid reservoir, but the response time is relatively slow.…”
Section: Mrf Mountmentioning
confidence: 99%
“…Therefore, the block-up behavior can be avoided by properly controlling the pressure difference (or the fielddependent actuating force) through the servo valve system. It is remarked here that recently, a new kind of high-loaded mount using MR elastomer was introduced in Yarra et al (2018). The mount based on the MR elastomer does not require any fluid reservoir, but the response time is relatively slow.…”
Section: Mrf Mountmentioning
confidence: 99%
“…Likewise, vibration, even in short period or low strength, can severely affect the performance of many sensitive electrical and optical instruments such as laser measurement systems, fiber sensing devices, and structural health monitoring equipment. Moreover, civil structures such as buildings, bridges, highways, traffic signals, and variable-message signs are susceptible to environmental stimulus such as wind, rain, vortex induced vibration (VIV), earthquakes, and storms, which enforce several levels of displacement and acceleration demands (Meyer et al, 2015; Yarra et al, 2018; Zhao et al, 2017). Furthermore, many human beings, according to their environmental work space, are at risk of excessive vibration which can lead to serious diseases such as hand-arm vibration syndrome (HAVS) (Yao et al, 2018), chronic back pain, spinal misalignment, and neck strain (Castelo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The MREs are, thus, considered to offer meritorious potentials for many engineering applications, particularly for vibration and noise reduction; thanks to their wide variations in stiffness and energy absorption properties, apart from the low response time, stability, compatibility with mechanical components and reasonably low power requirement (Li et al, 2014; Vatandoost et al, 2019). A number of studies have also demonstrated macroscopic applications of MREs such as vibration isolator for highway bridges (Yarra et al, 2018), vehicle seat suspensions (Du et al, 2011), powertrain mounts (Xin et al, 2016b), adaptive tuned vibration absorbers (ATVAs) (Qian et al, 2017; Sun et al, 2017), structural seismic mitigation as well microscopic applications such as force sensors (Li et al, 2009), soft actuator (Kashima et al, 2012), sealing eye retina detachments (Alekhina et al, 2018), MRE-based stiffness display (Hooshiar et al, 2020), and artificial lymphatic vessels (Behrooz, 2015). Besides, many semi-active MRE-based vibration suppression devices have been designed for applications in structural seismic mitigation (Gu et al, 2016, 2017, 2019; Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations